Factors influencing success / failure of reference interviews - Villalonga, Graciela T.; Faderon, Rosalie B.; Mallari, Florenda D. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2004)
This study was conducted to examine the factors affecting reference interview. specifically, it aimed to find out 1) the initial response and behavior of the library staff when asked reference questions and its impact on the questionnaire; 2) the strategy library staff used to respond to reference queries; 3) the predominant model of reference practice used by the library staff; 4) whether a follow-up question was used or not; and 5) the factors that contribute to the success or failure of the reference interview.
The descriptive survey method was used with the questionnaire as the main data-gathering tool. Descriptive statistics (frequency counts, percentages and mean averages) were employed in determining the objectives of this study.
Findings reveal that 1) majority of the library staff (58.73 percent) were free to assist when approached by the library users and those engaged in activities (such as assisting others, doing other work such as writing, cutting, pasting or in front of the computer) when approached still acknowledged the users' presence (76.19 percent); 2) library users are only fairly encouraged (3.7) by the initial response of the library staff; 3) the strategies that the library staff used to respond to users' queries are simply answering them without consulting any reference sources (that is, off the top of his/her head) (62.43 percent), giving instruction on or explaining how to use a reference source, computer, the library, etc. (48.68 percent), consulting reference sources (43.39 percent), and referring users to find the answers on their own (43.92 percent); 3) the predominant model of reference practice used by the library staff is self-service (53.44 percent) as majority of the library staff simply point the questionnaires to check the Web OPAC, bibliographic listings of reserve books, etc. or direct them to the place where the materials might be located; 4) the majority of the library staff did not ask the users any follow-up questions like whether they found what they were looking for or not (73.54 percent); 5) overall, library users are just marginally satisfied (3.5) with the performances of the library staff which were reflected in the fair ratings of the former gave on their approach, interviewing and listening skills and search strategy used; and 6) majority would still be willing to return to the same library staff for another question or help the next time around (63.49 percent).There is still a lot of room for improving the reference service and training further the front-line staff; there is a need to develop standards and guidelines for behavioral performance in reference service, for programs in communications training and long term plan to increase the number of staff to provide a satisfactory reference performance to the users.
Vita.
Special Problem (Master of Library Science)
Keywords: Reference services (Libraries) -- Philippines -- Diliman (Quezon City) -- Evaluation; Reference librarians -- Rating of -- Philippines -- Diliman (Quezon City).; Reference librarians -- Philippines -- Diliman (Quezon City) -- Attitudes